Доктрина отказа от права: опыт сравнительно- правового анализа - Sarkisyan, Arutyun (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the functioning of the notion of waiver in the civil law doctrine. The author present that act of one person that results in the surrender of a legal right in the context of comparative approach.